Bioconversion of Hospitality Food Waste Using Hermetia illucens Larvae: Effects of Food Waste Loading Rate and Larval Density on Waste Reduction and Biomass Production - Safikalianty, Bella; Lestari, Febrianti; Viruly, Lily (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2026)
Hospitality food waste constitutes a major fraction of organic waste generated by the hospitality sector and poses significant environmental challenges if not properly managed. This study evaluated the effectiveness of bioconversion of hospitality food waste using Hermetia illucens larvae in reducing organic waste and producing larval biomass, while also assessing the nutritional characteristics of bioconversion products. The experiment employed a completely randomized design with two factors, namely food waste loading rate (50, 200, and 400 g) and larval density (1, 4, and 8 g), resulting in nine treatment combinations. Bioconversion performance was evaluated based on organic waste reduction efficiency, larval biomass production, and kasgot formation. Proximate analysis was conducted at the end of the experiment using composite samples obtained from treatments with optimal bioconversion performance. Data were analyzed using two-way analysis of variance (ANOVA). The results showed that Hermetia illucens-based bioconversion effectively reduced hospitality food waste, achieving a maximum waste reduction efficiency of 93.66%. Higher substrate loading combined with lower larval density resulted in improved waste reduction efficiency and larval biomass production. Proximate analysis of the composite sample (duplicate analysis) indicated a protein content of 31.23%, total fat content of 39.65%, ash content of 14.31%, carbohydrate content of 11.20%, and a total caloric value of 526.64 kcal/100 g, demonstrating that nutritionally rich bioconversion products were generated under optimal treatment conditions. These findings indicate that Hermetia illucens-based bioconversion is an effective and sustainable approach for hospitality food waste management, capable of reducing organic waste while producing nutritionally valuable larval biomass.